Heat Treatment of Pitch Obtained from Atmospheric Fixed-Bed Coal Gasification - Phiciato Phiciato; Ika Monika; Arie Hardian (Universitas Gadjah Mada, 2018)
A medium temperature pitch obtained from atmospheric fixed-bed gasifier was distilled at a various time (1, 2, 3 and 4 h) to induce polymerization and the results were compared with a commercial pitch. Aromaticity level of pitches was examined using infrared spectroscopy, elemental analysis and simultaneous thermal analysis (TG-DSC). Longer heating time promoted lower moisture content, lower residue yield, higher insoluble fractions, as well as higher ash and carbon content. Although prolonged heat treatments lead to higher aromatization, there was no significant change in aromatization for heat treatment longer than 1 h. The index of aromaticity measured by using elemental analysis was ranged between 0.47 to 1.01, while the result from FTIR spectra showed stagnant value at 0.52. These values were slightly higher than that of pressurized Sasol-Lurgi gasification pitch (0.27).